Influence of Sex on Stroke Prognosis: A Demographic, Clinical, and Molecular Analysis - Rodríguez-Castro, Emilio; Rodríguez-Yáñez, Manuel; Arias, Susana; Santamaría, María; López-Dequidt, Iria; López-Loureiro, Ignacio; Rodríguez-Pérez, Manuel; Hervella, Pablo; Sobrino, Tomás; Campos, Francisco; Castillo, José; Iglesias-Rey, Ramón (Frontiers in Neurology, 2019)
Identifying the complexities of the effect of sex on stroke risk, etiology, and lesion progression may lead to advances in the treatment and care of ischemic stroke (IS) and non-traumatic intracerebral hemorrhage patients (ICH). We studied the sex-related discrepancies on the clinical course of patients with IS and ICH, and we also evaluated possible molecular mechanisms involved. The study’s main variable was the patient’s functional outcome at 3-months. Logistic regression models were used in order to study the influence of sex on different inflammatory, endothelial and atrial dysfunction markers. We recruited 5,021 patients; 4,060 IS (54.8% male, 45.2% female) and 961 ICH (57.1% male, 42.9% female). Women were on average 5.7 years older than men (6.4 years in IS, 5.1 years in ICH), and more likely to have previous poor functional status, to suffer atrial fibrillation and to be on anticoagulants. IS patients showed sex-related differences at 3-months regarding poorer outcome (55.6% women, 43.6% men, p<0.0001), but this relationship was not found in ICH (56.8% vs. 61.9%, p=0.127). In IS, women had higher levels of proBNP and 3-months worse outcome in both cardioembolic and non-cardioembolic stroke patients. Stroke patients showed sex-related differences in prehospital data, clinical variables and molecular markers, but only IS patients presented independent sex-related differences in 3-months poor outcome and mortality. There was a relationship between the molecular marker of atrial dysfunction proBNP and worse functional outcome in women, resulting in a possible indicator of increased dysfunction.